2015
DOI: 10.1007/s00270-015-1156-6
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Management of Acute Embolic Occlusion of the Superior Mesenteric Artery: A 12-Year Single-Centre Experience

Abstract: Primary endovascular therapy for acute embolic SMA occlusion with on-demand laparotomy is a recommended algorithm used in our centre to treat SMA occlusion. This combined approach for the treatment of AMI is associated with in-hospital mortality rate of 27.0 %.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
23
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(36 citation statements)
references
References 26 publications
3
23
1
3
Order By: Relevance
“…Eighteen papers met the inclusion criteria and were included in this systematic review. All the data collected by 12 studies focusing on acute arterial mesenteric ischemia are summarized in Table 1 [ 2 - 14 ], and the data obtained from 6 papers focusing on acute venous mesenteric ischemia are presented in Table 2 [ 15 - 20 ]. In Tables we analyzed all studies published during the selected period (2005-2016).…”
Section: Resultsmentioning
confidence: 99%
“…Eighteen papers met the inclusion criteria and were included in this systematic review. All the data collected by 12 studies focusing on acute arterial mesenteric ischemia are summarized in Table 1 [ 2 - 14 ], and the data obtained from 6 papers focusing on acute venous mesenteric ischemia are presented in Table 2 [ 15 - 20 ]. In Tables we analyzed all studies published during the selected period (2005-2016).…”
Section: Resultsmentioning
confidence: 99%
“… 7 , 8 Endovascular treatment has the advantages of minimal invasiveness, fewer post-operative complications, and lower mortality rates than open surgery. 8 , 9 , 10 Arthurs et al. reported that patients with AMI receiving endovascular treatment and undergoing open surgery had mortality rates of 36% and 50%, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…The anterior approach near the root of the mesentery is most suitable for embolectomy whereas the lateral approach, with mobilization of the fourth part of duodenum and ligament of Treitz, is often preferred for arterial bypass (figures 5,6). Selection between these two approaches depends on the diagnosis (embolus versus thrombosis) and the need for complex arterial reconstruction.…”
Section: Open Surgical Revascularizationmentioning
confidence: 99%